Synthesis and in vitro cytotoxic evaluation of new quinazolinone-based conjugates - Vu, Tran Khac; Linh, Nguyen Huong; Duc, Ta Hong; Cuong, Ho Duc (Vietnam Journal of Science and Technology, 2021)
A series of new quinazolione derivatives containing a conjugate sytem 13 a-l were synthesized via a three step-procedure. The first step is the condensation of 5-hydroxyanthranilic acid (10) at 160oC for 2 h to afford the intermediate 11 in high yield. This intermediate was then reacted with n-butylamin in acetic acid at 160oC for 14 h to give 12 in 92%. Finally, the reaction of 12 with different aldehydes in acetic acid at 140oC for 14h furnished new conjugates 13a-l in 62-81%. The bioassay results showed that several compounds displayed cytotoxic effect against two cell lines including HepG-2 and SKLu-1 in which 13h exhibited the strongest cytotoxic effect against SKLu-1 with IC50 value of 5.05 µg/mL.